Synergy between in-situ immobilized MoS2 nanosheets and TiO2 nanotubes for efficient electrocatalytic hydrogen evolution. (12th January 2022) - AlAqad, Khaled M.; Kandiel, Tarek A.; Basheer, Chanbasha
Abstract: MoS2 electrocatalyst exhibits a significant potential to substitute platinum in hydrogen evolution reaction (HER), but its immobilization on practical supports is still challenging. Herein, a facile hydrothermal method is developed for in-situ immobilizing MoS2 nanosheets on titanium nanotubes (TNTs) support. Easy to mount electrodes with a uniform and dense layer of MoS2 on TNTs are achieved. An overpotential of −200 mVRHE is ample to deliver −10 mA/cm 2 from an acidic medium. This overpotential is much lower than those of the electrodes developed by drop-casting MoS2 on TNTs, glassy carbon (274 mV), and in-situ immobilized on Ti foil (264 mV). The results revealed that the synergy between the in-situ immobilized MoS2 and TNTs enhances the electrochemical surface area and the adsorption capacity of hydronium ions. The electronic interaction between MoS2 and TNTs facilitates the mobility of electrons and reduces the charge transfer resistance at the electrode/electrolyte interface. Highlights: TNTs have been investigated as support for MoS2 HER electrocatalyst. Self-assembled MoS2 nanosheets have been in-situ immobilized on TNTs support. Synergy between MoS2 and TNTs has been observed. TNTs facilitate the electron transfer to the MoS2 HER electrocatalyst. TNTs enhance the electrochemical surface area and H3 O + ions adsorption capacity. Graphical abstract: Image 1